(untitled) (Journal of Computational Mathematics, 1994)
A fast algorithm for evaluating and displaying bivariate splines in a three direction is presented based on two-level transformation of the corresponding of the corresponding B-splines. The efficiency has been shown by experiments of surface modelling design.